Immunometabolism and Covid-19: Could Lifelong Exercise Training Have a Protective Effect? - Minuzzi, Luciele Guerra [UNESP]; Teixeira, Ana Maria; Thomatieli-Santos, Ronaldo V.; Rosa-Neto, José C.; Lira, Fábio S. [UNESP] (Wolters Kluwer, 2021)
The world is experiencing a severe new pandemic, in which the elderly afflicted with chronic diseases are the most affected. The aging of the immune system (immunosenescence) reduces its efficacy against viral infections and increases its susceptibility to repeated acute infections, such as the flu. The improvement of the immune system functioning leading to a reduced incidence of infections can be achieved with regular physical exercise, besides its countless other benefits. The immunosenescence delay in master athletes, protecting them from possible viral infections, has been recently shown. Here the role of aerobic exercise training as an immune system fine-tuning regulator was discussed, focusing on lifelong athletes and specifically on the age-impaired antibody production in immunized elderly and the effects of lifelong physical exercise on the anti-inflammatory and vaccine response optimization. Moreover, the aerobic training effects on the natural killer (NK) cell activity and the underlying mechanisms responsible for a better antiviral response in active elderly and/or master athletes were addressed. It was hypothesized that lifelong exercise training delays age-related decrements in immunity by remodeling the metabolism of different cells (e.g., NK cells), creating a metabolic scenario that in turn improves the immune system’s viral response. Lifelong exercisers present a preserved immune response to exercise, indicating that they are better prepared to respond to new immune challenges. Thus, master athletes and lifelong exercisers are possibly protected against or could mitigate the COVID-19 disease.
Keywords: COVID-19; exercise training; master athletes; NK cells; viral infections